Microsurgical denervation of the spermatic cord for treatment of idiopathic chronic orchialgia - Tu, Xiang-An; Gao, Yong; Zhang, Ya-Dong; Zhuang, Jin-Tao; Zhao, Ji-Quan; Zhao, Liang-Yun; Zhao, Liang; Sun, Xiang-Zhou; Qiu, Shao-Peng; Deng, Chun-Hua (Chinese medical journal, 2012)
A patient referred to our hospital, diagnosed with left idiopathic chronic orchialgia, was evaluated with a thorough medical and psychiatric history, physical examination, scrotal ultrasound and magnetic resonance imaging. Conservative management failed. The patient had temporary pain relief after undergoing outpatient cord block three times. Microsurgical denervation of the left spermatic cord was operated in March, 2011. A pain questionnaire was used to determine efficacy before and after operation, and complete pain relief was noted at one week after operation. The follow up period was 12 months, at the end of which the pain score was still zero. No complications, including testicular atrophy and hydrocele, occurred. Microsurgical denervation of the spermatic cord can be a minimally invasive, safe and effective management option for treatment of idiopathic chronic orchialgia.